Yrjö Kukkapuro furniture designer - Hai, Fang (Nanjing : Southeast University Press, 2001)
The Finnish furniture designer Yrjö Kukkapuro (b. 1933) is a central figure of Finnish functionalism. Kukkapuro has been working as a freelance designer since the 1950s and much of the furniture he designed at the beginning of his career is still in production.These days Yrjö Kukkapuro designs mostly for the company Avarte. His most famous pieces of furniture are the Karuselli chair, the Saturnus table, the Skaala chair, the Remmi series and the Ateljee lounge chair and sofa. One of Kukkapuro’s favourite sayings is “Does it make any sense to design a chair which is not good to sit on?” and it describes very well the designer’s love for ergonomic furniture.
Adlib record nr. 530009573
persoonlijk dededicaceerd 'to lieven daenens 26-04-2002' gevolgd door de handtekening van Kukkapuro
Engels
boek
Keywords: Kukkapuro, Yrjö; eigen tijd; Finland